Analysis of linear circuits with real operational amplifier - Kostromitsky, Andrew (Видавництво Львівської політехніки, 2012)
The technique and main principles of the analysis of linear circuits on operational amplifiers, allowing to take into account the frequency characteristic of the real operational amplifier. Features of the analysis of circuits of zero, first and second orders are specified. The universal method of designing of the filters is offered.
Keywords: Operational amplifier; Filters; Frequency characteristic; Topological model